The Impact of Human Resources Management Strategy on the Quality of Health Services at Al-Hawari Hospital, Benghazi, Libya - Rania Madi; Eman Emsemeir; Lamya El Adouli; Eman Haslok; Salema Al-Zwey; Galeda Elsahar; Hend Almajbri (AlQalam Journal of Medical and Applied Sciences, 2025)
The study examines the impact of Human Resources Management (HRM) strategy on the quality of healthcare services at Al-Hawari General Hospital in Benghazi, Libya. The hospital, a representative healthcare institution, was selected from a group of major hospitals in the city. The research adopted a descriptive analytical approach to examine the relationship between HRM practices and the perceived quality of healthcare service delivery. The study involved 248 individuals, including medical personnel, allied medical professionals, and administrative staff. The data collection was conducted using an anonymized questionnaire with closed-ended questions formatted on a five-point Likert scale. The findings reveal that the workforce at Al-Hawari General Hospital is predominantly female (67.1%) and largely composed of individuals aged 25-30 years, with most having 5-6 years of professional experience. Despite the hospital’s commitment to quality improvement, approximately 80% of the medical and paramedical staff reported challenges in delivering high-quality care. 30.5% of respondents expressed dissatisfaction with hospital management’s efforts to encourage staff development and innovation. However, 43.5% of participants recognized a moderate positive relationship between the implementation of HRM strategies and improvements in healthcare quality. In conclusion, the study emphasizes the importance of aligning HRM strategies with adequate resource support to enhance healthcare service quality.